Implementasi Kebijakan Tentang Proses Belajar Mengajar di Sekolah - Rafki Parifia; Alexa Ayu Dewanda; M. Taura Zilhazem; Fathur Rahman; Sakban Sakban (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The implementation of educational policies in schools plays a pivotal role in improving the quality of teaching and learning processes. The success of these policies is determined by the readiness of educational institutions, the professional competence of teachers, and the active involvement of various supporting stakeholders. Each of these elements significantly contributes to the effectiveness of learning outcomes in the classroom. However, policy implementation often faces challenges such as inadequate infrastructure, lack of comprehensive teacher training, and a mismatch between national policies and the specific needs of local educational contexts. In this regard, schools must be able to adapt policy frameworks to suit their unique environments, ensuring that the goals of the policy are effectively aligned with students’ learning needs. Teachers play a central role as key implementers who are not only required to understand the substance of educational policies but also to apply them creatively and contextually in their classrooms. Their ability to interpret and operationalize these policies directly affects the quality of educational delivery. Furthermore, continuous evaluation is essential to measure the extent to which policies have been effectively implemented. This evaluation process serves not only as a feedback mechanism but also as a basis for future policy adjustments and improvements. It enables stakeholders to identify gaps, assess outcomes, and refine strategies to ensure sustainable educational development. In conclusion, effective policy implementation requires a holistic approach that involves institutional preparedness, teacher capability, stakeholder support, contextual adaptation, and ongoing evaluation. Without these elements working in synergy, even well-formulated policies may fall short in achieving their intended impact on educational quality and student success.